A louca autofágica: a invenção de si na escrita de Maura Lopes Cançado em hospício é Deus - diário I (1965) - Augusto, Carolina de Fátima Linhares (2025)
This study aims to analyze Maura Lopes Cançado’s diary, Hospício é Deus: diário I (1968), written during her confinement at the Gustavo Riedel asylum (Rio de Janeiro), as a literary movement of self-invention through the practices of self-writing. Drawing on Philippe Lejeune’s work on autobiography and the diary, as well as Mikhail Bakhtin’s reflections on speech genres, this research investigates how the author employs this intimate writing form to fictionalize herself as a “mad” writer. By choosing the diary as her discursive form, Maura also adopts the foundational characteristics of the genre—those that shape its structure and enable it to convey a particular kind of enunciation—chief among them, sincerity. The hypothesis is that this fictional exercise stems from a desire to invent herself as a great writer, using the diary and madness as a means of affiliating herself with authors she explicitly mentions in her intimate writing, such as Dostoevsky, Sartre, and Clarice Lispector. From this starting point, Maura’s writing may be understood as a deliberate literary construction: she selects, edits, narrates, and publishes, navigating the inherent fissures of the genre and playing the “game of sincerity,” thus crafting a credible character. The research connects this inventive process to its critical reception following the publication of the diary, considering that Maura had already published in Jornal do Brasil and was connected to writers such as Reynaldo Jardim, Assis Brasil, and Ferreira Gullar. Her diary was read and, apparently, well received by the literary critics of Rio de Janeiro. Analyzing this reception is crucial to understanding how her fictional endeavor was interpreted. In this sense, and once again drawing on Bakhtin’s theoretical contributions, the diary is conceived as a space in which time takes form—becoming part of its movement and integrating itself into the narrative as a mode of perceiving the surrounding world. The research thus seeks to investigate the diary as the embodiment of “madness-time,” a mode of experiencing the passage of time within the asylum.